A Memory of Ice The Antarctic Voyage of the Glomar Challenger - Truswell, Elizabeth (ANU Press, 2019)
"In the southern summer of 1972/73, the Glomar Challenger was the first vessel of the international Deep Sea Drilling Project to venture into the seas surrounding Antarctica, confronting severe weather and ever-present icebergs. A Memory of Ice presents the science and the excitement of that voyage in a manner readable for non-scientists. Woven into the modern story is the history of early explorers, scientists and navigators who had gone before into the Southern Ocean. The departure of the Glomar Challenger from Fremantle took place 100 years after the HMS Challenger weighed anchor from Portsmouth, England, at the start of its four-year voyage, sampling and dredging the world's oceans. Sailing south, the Glomar Challenger crossed the path of James Cook's HMS Resolution, then on its circumnavigation of Antarctica in search of the Great South Land. Encounters with Lieutenant Charles Wilkes of the US Exploring Expedition and Douglas Mawson of the Australasian Antarctic Expedition followed. In the Ross Sea, the voyages of the HMS Erebus and HMS Terror under James Clark Ross, with the young Joseph Hooker as botanist, were ever present. The story of the Glomar Challenger's iconic voyage is largely told through the diaries of the author, then a young scientist experiencing science at sea for the first time. It weaves together the physical history of Antarctica with how we have come to our current knowledge of the polar continent. This is an attractive, lavishly illustrated and curiosity-satisfying read for the general public as well as for scholars of science."